Increased Addes Value Msmes Through Innovation Management in Entrepreneurship - Sugeng Santoso; Antonius Setyadi; Muhammad Ramadhani Marfatah; Juli Simon Macariola; Jehan Reza Ananda; Nurahma Sabila (DIKDIMAS : Jurnal Pengabdian Kepada Masyarakat, 2024)
The existence of a community among MSMEs/creative economy actors is an important thing that needs to be considered in innovation, to meet consumer needs. This Community Service aims to strengthen the capacity of MSMEs in understanding innovation management in entrepreneurship. The scope of PkM is intermediation with MSMEs/creative economy actors for the products/services produced to be accepted by users, understanding, knowledge of creativity and innovation management are needed. The method used uses a qualitative approach through participatory discussions during the implementation of PkM, pre-survey - participatory observation, and interviews with key informants and main informants and supporting informants. The analysis used in this article is qualitative data analysis, namely measuring knowledge of innovation and providing suggestions/input for improvements so that it can be followed up by MSME players. The output of this Community Service is to increase the community's understanding and skills in understanding the creativity and innovation of the products they produce because so far most of them do not have an understanding of innovation management in entrepreneurship. The results of the PkM are that UKM guidance, namely output officials, will follow up on these outcomes and be accompanied by UMB lecturers. The conclusion is that MSME actors in Meruya Selatan Subdistrict do not yet understand the importance of creativity and innovation, including market changes (user) needs, technological developments and innovations that can be used in the business value chain (entrepreneurship) as well as the use of digital in entrepreneurship, especially digital transformation for marketing channels.